A biparameterized analysis of integral inequalities for bounded and holderian mappings - Benchettah, Djaber Chemseddine,; Meriem, Bouchareb; Abdelghani, Lakhdari; Badreddine, Meftah (Journal of Innovative Applied Mathematics and Computational Sciences, 2024)
In this study, we introduce a new parameterized identity that generates a series of Newton-Cotes formulas for one, two, three, and four points. We then derive several novel Newton-Cotes-type inequalities for functions with bounded and rr-LL-Hölderian derivatives. The research is finalized with numerical examples and graphical illustrations that validate the precision of our findings.